(untitled) (Bulletin KNOB, 2006)
Architectural-historical research only contributes to a limited extent to the solution of practical problems during restorations. Preliminary thorough building-historical research is not always a matter of course. Moreover, the subject of history of building construction is lagging behind in comparison with the countries around us. In the Netherlands applied research of historic buildings particularly proceeds from the (governmental and municipal) departments of preservation of monuments and historic buildings and from private initiative. Hardly any building-historical research is taking place within the walls of the Dutch universities, no matter whether it concerns the technical sciences or the humanities. A building-historical research programme is completely non-existent, and so is adequate scientific support. As long as traditional architectural history is not aware of the importance of a material and constructive approach to a building, the gap between theory and practice will continue to exist. More interdisciplinary cooperation between building- and architectural history could change this situation. The fact that the postgraduate higher vocational education Building History and Restoration in Utrecht - for which those interested pay many thousands of euros out of their own pockets - and also that the internationally highly renowned postgraduate education Preservation of Monuments and historic Buildings at the Raymond Le Maire centre in Leuven can count on considerable interest, proves that there is a demand for it.